A Semiotic Analysis of Cultural Values in British and American Game Shows Using Roland Barthes’ Theory - M. Gian Fathi Priyatama; M Afifulloh (Humanitatis : Journal of Language and Literature, 2026)
This study examines game shows as a form of popular culture that functions not only as entertainment but also as a medium for reflecting and disseminating the social values of their countries of origin. In the context of globalization, the strong influence of British and American entertainment industries has enabled their game shows to reach global audiences while implicitly transmitting particular cultural ideologies. Using a descriptive qualitative method and Roland Barthes’s semiotic framework, this research analyzes the meanings of denotation, connotation, and myth in two iconic programs, Who Wants to Be a Millionaire? (UK) and Jeopardy! (US). The findings reveal that each show embodies distinct cultural values. The British program tends to emphasize self-control, politeness, and social hierarchy, reflected in the formal interactions between the host and contestants and in the game’s overall restrained structure. By contrast, the American show highlights individualism, aggressive competition, and materialism, as seen in its dramatic presentation and strong focus on personal achievement. At the mythic level, the American program is dominated by narratives of “instant success” and the “American Dream.” In contrast, the British program more strongly projects myths of “social justice” and a “dignified process.” These findings suggest that game shows operate as vehicles of cultural ideology, with the values they promote reflecting the social identity and structure of each nation.